Biogenic Silver Nanoparticles Can Control Toxoplasma gondii Infection in Both Human Trophoblast Cells and Villous Explants - Costa, Idessania Nazareth; Ribeiro, Mayara; Silva Franco, Priscila; da Silva, Rafaela José; de Araújo, Thádia Evelyn; Milián, Iliana Claudia Balga; Luz, Luana Carvalho; Guirelli, Pâmela Mendonça; Nakazato, Gerson; Mineo, José Roberto; Mineo, Tiago W. P.; Barbosa, Bellisa Freitas; et al. (Frontiers in Microbiology, 2021)
The combination of sulfadiazine and pyrimethamine plus folinic acid is the conventional treatment for congenital toxoplasmosis. However this classical treatment presents teratogenic effects and bone marrow suppression. In this sense new therapeutic strategies are necessary to reduce these effects and improve the control of infection. In this context, biogenic silver nanoparticles (AgNp-Bio) appear as a promising alternative, since they have antimicrobial, antiviral and antiparasitic activity. The purpose of this study to investigate the action of Biogenic Silver Nanoparticles in BeWo cells, HTR-8/SVneo cells and villous explants and its effects against T. gondii infection. Both cells and villous explants were treated with different concentrations of AgNp-Bio or combination of sulfadiazine + pyrimethamine (SDZ+PYZ) in order to verify the viability. After, cells and villi were infected and treated with AgNp-Bio or SDZ+PYZ in different concentrations to ascertain the parasite proliferation and cytokine production profile. AgNp-Bio treatment did not reduce the cell viability and villous explants. Significant reduction was observed in parasite replication in both cells and villous explants treated with Silver Nanoparticles and classical treatment. The AgNp-Bio treatment increased of IL-4 and IL-10 by BeWo cells, while HTR8/SVneo cells produced MIF and IL-4. In the presence of T. gondii, the treatment induced high levels of MIF production by BeWo cells and IL-6 by HTR8SV/neo. In villous explants, the AgNp-Bio treatment down-regulated production of IL-4, IL-6 and IL-8 after infection. In conclusion, AgNp-Bio can decrease T. gondii infection in trophoblast cells and villous explants. Therefore, this treatment demonstrated the ability to reduce the T. gondii proliferation with induction of inflammatory mediators in the cells and independent of mediators in chorionic villus which we consider the use of biogenic silver nanoparticles promising in the treatment of toxoplasmosis in BeWo and HTR8 / SVneo cell models and in chorionic villi.